1976
DOI: 10.1037/0097-7403.2.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous and backward fear conditioning as a function of number of CS-UCS pairings.

Abstract: Four experiments examined the possibility that the outcome of simultaneous and backward fear conditioning procedures might depend upon the number of CS-UCS pairings. A punishment procedure will rats as subjects and shock as the UCS was used; the amount of suppression produced by response-contingent CS presentations indexed the strength of acquired fear. Experiments 1, 3, and 4 examined the suppressive tendencies of simultaneous-and backward-trained CSs after 0, 10, 20, 40, 80, and 160 pairings. The pattern of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
97
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 28 publications
(36 reference statements)
10
97
0
Order By: Relevance
“…The present evidence that a backward conditioning procedure can produce reliable excitatory conditioning is in agreement with a number of empirical and theoretical articles (Cautela, 1965 ;Champion & Jones, 1961;Heth, 1976 ;Hcth & Rescorla, 1973;Mahoney & Ayres, 1976;Matsumiya, 1960;Mowrer & Aiken, 1954;Terry & Wagner, 1975). Moreover, this investigation has demonstrated that the US intensity parameter is a critical determinant of such conditioning.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The present evidence that a backward conditioning procedure can produce reliable excitatory conditioning is in agreement with a number of empirical and theoretical articles (Cautela, 1965 ;Champion & Jones, 1961;Heth, 1976 ;Hcth & Rescorla, 1973;Mahoney & Ayres, 1976;Matsumiya, 1960;Mowrer & Aiken, 1954;Terry & Wagner, 1975). Moreover, this investigation has demonstrated that the US intensity parameter is a critical determinant of such conditioning.…”
Section: Discussionsupporting
confidence: 75%
“…Recently, a number of studies (Heth , 1976 ;Heth & Rescorla, 1973;Mahoney & Ayres, 1976) have demonstrated reliable excitatory effects in a backward fear conditioning paradigm. Although the differences between backward and control groups in each of these studies were significant, the levels of conditioning obtained in the one-trial backward conditioning procedure by Mahoney and Ayres (1976) were extremely small, and no replication of their results has since been reported.…”
mentioning
confidence: 99%
“…One potential objection to this interpretation is that it demands that simultaneous pairings of two associatively-activated event representations resulted in inhibition. Although this possibility may seem unlikely, there is evidence that simultaneous first-order conditioning can yield inhibition after extensive training (e.g., Heth, 1976;Moscovitch & LoLordo, 1972). The results of Experiments 1a and 1b might stand as an analogous situation in which simultaneous activation of two representations led to a net inhibitory relationship.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, if the tone preceded the noise, one might expect inhibitory learning similar to that observed in Experiments 1a and 1b. These expectations are based on the knowledge that consistent forward CS→US pairings result in excitatory learning (e.g., Pavlov, 1927), whereas backward US→CS conditioning typically results in the development of inhibition (e.g., Cole & Miller, 1999;Chang, Blaisdell, & Miller, 2003;Delamater, Lolordo, & Sosa, 2003;Heth, 1976;Williams & Overmier, 1988), often after a brief period of excitatory learning.By contrast, within the MSOP account outlined previously, the temporal arrangement of noise and tone in Phase 2 might have little effect on whether noise forms an excitatory or inhibitory association with sucrose. In all cases, pairings of two associatively-activated event representations would result in excitatory learning between those representations.…”
mentioning
confidence: 99%
“…Pavlov's (1927, p. 393) revised view that the backward CR is transitory and limited to the early stages of training finds support in current research with conditioned suppression (Heth, 1976;Mahoney & Ayres, 1976). In contrast, however, both Beritoff (1965) and Asratyan (1972) have reported that the backward CR may benefit from extended training-a view that finds some support in research with the Pavlovian procedure (Harlow, 1939;Wagner & Terry, 1975).…”
Section: Methodsmentioning
confidence: 39%